다중속성 의사결정 기반 도로 포장재료 선정 사례연구 - 박진영; 고태용; 박영준; 이창용; Park, Jin-Young; Go, Tae-Yong; Park, Young-Jun; Yi, Chang-Yong (한국건설관리학회 논문집, 26(2), 2025)
As global warming intensifies, the Korean government has declared achieving carbon neutrality by 2050 as a national goal and has announced a carbon neutrality scenario to achieve net-zero domestic carbon emissions. This effort demonstrates Korea's commitment as a member of the global community to jointly reduce greenhouse gases. Achieving this goal requires a shift to an eco-friendly construction industry. However, the decision-making process for construction projects often considers only economic feasibility. In this study, we evaluated the overall performance of pavement materials in a case project using a multi-attribute decision-making model that considers both cost and environmental impacts. While cement concrete was initially selected as a favorable alternative based solely on economic feasibility during the design stage, environmental assessments revealed that it imposes about 1.5 times more environmental burden than asphalt concrete. Thus, asphalt concrete emerged as a more environmentally favorable material. When both cost and environmental impacts were applied to the multi-attribute decision-making model, asphalt concrete was selected as the favorable pavement material, satisfying both economic feasibility and eco-friendly criteria. This finding indicates that decision-making outcomes may change when environmental impacts are considered. The study presents a simple yet rational methodology that can be effectively utilized in the decision-making processes of domestic construction projects, contributing to a paradigm shift in decision-making. This is expected to enhance the quality of decision-making for achieving carbon neutrality and promote the development of sustainable construction technologies. 지구온난화가 심화되면서 한국정부는 2050년 탄소중립 달성을 국가 목표로 천명하고 국내 탄소 순배출량을 '0'으로 하는 탄소 중립 시나리오를 발표하여 지구공동체 일원으로서 온실가스 감축을 위한 공동노력을 실천하고 있다. 이 목표를 달성하기 위해서는 친환경 건설산업으로의 전환이 필요하다. 그러나 건설 프로젝트의 의사결정 과정에는 경제성에 대한 분석만을 고려하는 경우가 많다. 이 연구에서는 사례 프로젝트의 포장재료를 대상으로 경제성과 환경영향을 모두 고려할 수 있는 다중속성 의사결정 모델을 사용하여 종합성능을 평가하였다. 경제성만을 고려한 사례 프로젝트의 설계단계 의사결정에서 시멘트콘크리트가 선호할 만한 대안으로 선정되었으나, 환경영향 평가에서 시멘크콘크리트는 아스팔트콘크리트 보다 약 1.5배의 환경부하가 더 발생하는 것으로 분석되어 경제성 평가결과와 반대로 아스팔트콘크리트가 환경적으로 선호할 만한 재료임을 보였다. 경제성과 환경영향 평가결과를 다중속성 의사결정 모델에 적용한 결과 아스팔트콘크리트가 경제성과 친환경성을 모두 만족하는 포장재료로 선정되어 환경영향이 함께 고려될 경우 의사결정 결과가 달라질 수 있음을 보였다. 이 연구는 국내 건설사업의 의사결정 과정에서 유용하게 활용할 수 있는 간단하면서도 합리적인 방법론을 제시하였으며, 의사결정과 관련한 패러다임의 변화를 유도하는 데 기여할 것이다. 이는 탄소중립 실현을 위한 의사결정의 질을 향상시키고 지속가능한 건설기술의 개발을 촉진할 수 있을 것으로 기대한다.